2015
DOI: 10.1111/ppe.12252
|View full text |Cite
|
Sign up to set email alerts
|

Possible Common Aetiology behind Maternal Preeclampsia and Congenital Heart Defects in the Child: a Cardiovascular Diseases in Norway Project Study

Abstract: Early-onset preeclampsia was strongly associated with infant risk of severe CHD, specifically; the risk of AVSD was 15-fold higher if the mother was diagnosed with early-onset preeclampsia, suggesting common aetiological factors for early-onset preeclampsia and erroneous fetal heart development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 36 publications
2
52
0
3
Order By: Relevance
“…There is coincidence of both CHD and preterm PE in about five per 100 000 pregnancies. The epidemiological studies highlighting the association between fetal CHD and PE reported that the increased risk affected mainly the rate of early PE with delivery at < 34 weeks' gestation [6][7][8] . However, the incidence of such early PE in the general population is very low (0.2-0.3%) 7,8 and, even with a seven-fold increased incidence of cases of fetal CHD 8 , the expected incidence in such cases would be only 1-2%.…”
Section: Main Findings Of Studymentioning
confidence: 99%
“…There is coincidence of both CHD and preterm PE in about five per 100 000 pregnancies. The epidemiological studies highlighting the association between fetal CHD and PE reported that the increased risk affected mainly the rate of early PE with delivery at < 34 weeks' gestation [6][7][8] . However, the incidence of such early PE in the general population is very low (0.2-0.3%) 7,8 and, even with a seven-fold increased incidence of cases of fetal CHD 8 , the expected incidence in such cases would be only 1-2%.…”
Section: Main Findings Of Studymentioning
confidence: 99%
“…With the aggravation of the disease, the expression of miRNA-376c in patients with severe PE was significantly decreased compared with those in other groups, the fetal weight was small and most fetuses were premature. It has been reported in the literature (24) that the risks of neonatal defect disease and premature delivery are higher in PE patients.…”
Section: Discussionmentioning
confidence: 99%
“…Auger y cols reportaron una asociación significativa entre la PE de inicio temprano y el desarrollo de CC de tipo crítico con una razón de prevalencia de 2,78 (IC95% 1,71-4,50), una diferencia de prevalencia de 249,6 en 100.000 y un RR ajustado de 2,8 (IC95% 1,8-4,4). Por otro lado, Brodwall y cols reportaron que la PE de inicio temprano tanto leve como severa estuvieron asociados con un incremento de riesgo de CC con un RR de 15,5 (IC95% 7,9-30,4) y un RR ajustado de 13,5 (IC95% 6,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]8), especialmente con la doble salida del ventrículo derecho (double outlet right ventricle, DORV), síndrome de corazón derecho hipoplásico (hypoplastic right heart síndro-me, HRHS), coartación de la aorta y con defecto del tabique auriculoventricular (atrioventricular septal defect, AVSD); esta última, presente en más del 25% de los casos de PE de inicio temprano severo. Solo se encontró un incremento de riesgo de CC en el grupo de PE severa tardía con un RR de 1,7 (IC95% 1,2-2,4).…”
Section: Discussionunclassified
“…Brodwall y cols (11) limitaron su estudio a casos de CC severa, entre los que se incluyeron: heterotaxia, transposición de grandes vasos, tetralogía de Fallot, DORV, otros defectos conotruncales (estenosis aórtica supravalvular, defecto del tabique ventricular (ventricular septal defects, VSD), tronco arterial común, arco aórtico interrumpido), AVSD, retorno venoso pulmonar anómalo, hipoplasia del corazón izquierdo, estenosis valvular aórtica, HRHS, anomalía de Ebstein. Por otro lado, Auger y cols (10) clasificaron a las CC en críticas y no críticas, incluyendo en el primer grupo: tetralogía de Fallot, transposición de grandes vasos, tronco arterial, hipoplasia del corazón izquierdo, coartación aórtica.…”
Section: Discussionunclassified